The spatial pattern of voter choice homogeneity in the Nigerian presidential elections of the fourth republic - Nwankwo Cletus Famous (Bulletin of Geography. Socio-Economic Series)
The return of democratic rule in 1999 after many years of military intervention has left some electoral geographic imprints on Nigeria: voting pattern has varied over this period. This paper analyses the pattern of voter choice homogeneity (VCH) and tests the effect of religion on VCH in the presidential elections of the fourth Nigerian republic from 1999 to 2015. The study found that some economic indicators have a positive and significant effect on VCH from the 2003 election but were all insignificant and with a negative impact in the 2015 election. The influence of religion on VCH was negative in the 1999 election but remained positive in subsequent elections and had an increasingly upward trajectory signifying the snowballing importance of faith in citizens’ political choices at the presidential polls. The analysis shows that the pattern of VCH in 1999 was random, but clustered from 2003 to 2015, although the 2011 geographical clustering of VCH was dissected and the 2015 pattern was regionalised. Thus, the article argues that voting patterns structured Nigeria’s political landscape from a random to clustered but dissected electoral landscapes to a clustered but regionalised mi-lieu of a nation of two voting worlds. The pattern of a nation of two voting blocs was witnessed in the 2015 election, in which the VCH sharply depicts the religious cleavage of the country and to some degree also depicts ethnic fault-lines.